FIGURATIVE LANGUAGE IN MOVIE SCRIPT ‘ME BEFORE YOU’ - Ni Luh Sriwedani; Fivy Andries; Veronika Damopolii (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aimed to identified, classified and analyzed the types and functions of figurative language that used in a movie entitled Me Before You. In conducted this research, the writer used a descriptive qualitative method. The data was gathered from character interactions in a form of movie script. As a result, 28 data of figurative language in the movie was found, the writer used the theory that was proposed by McArthur (1992) in analyzed and classified the type of figurative language, there are 4 data that classified as simile type, 1 datum as a metaphor type, 19 data as hyperbole type, 4 data as personification type and there is no data found that has repetition type of figurative language. Referred to the theory of figurative language functions that was proposed by Perrine (1969), in this research, the writer found that there are 12 data of figurative language served to afford imaginative pleasure, 8 data found functioned to bring an additional imagery, 3 data found to add emotional intensity and 5 data found of figurative language in the movie served to say much in brief.